Determinants of bank performance in Malaysia - Siew-Peng, Lee (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
This study examines the extent to which CAMEL variables, bank-specific factors, corporate governance and macroeconomic factors influence the performance of banks in Malaysia. Three-panel data models are used for analysis, which is the pooled ordinary least squares, random effects and two-step GMM models over the period 2003 to 2016. The results indicate that capital strength, bank size, remuneration of the board of directors, the duality of the CEO-chairman and economic growth have a positive effect on bank performance, whereas management efficiency, liquidity and loan growth have a negative effect on performance. The findings suggest that the performance of banks is affected not only by bank-specific factors but also by governance and macroeconomic factors. Evidence on the relationship between governance and performance indicates that increasing the number of independent directors is simply not enough to influence performance. Our findings provide justification for regulators to consider having a set of eligibility specifications to become a bank director to ensure that governance in the banking industry is further strengthened.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 311-335
Keywords: bank performance; CAMEL variables; corporate governance; return on assets; Malaysian banks